Critical Discourse Analysis of Gender Construction on Islamic History Content in the Islamic Religious Education Textbook for Junior High School - Wicaksono, Mochammad Jiva Agung; Nurmila, Nina; Arifin, Bambang Samsul; Karman, Karman (Jurnal Pendidikan Agama Islam, 2021)
Schools are one of the most effective places to make humans free from all forms of oppression. Unfortunately, the textbooks used in schools contain a lot of gender inequality. This study aims to understand how the content of Islamic History in the Islamic Education textbook constructs gender which has implications for gender-based injustice. This study uses a qualitative approach with the method of critical discourse analysis by Norman Fairclough’s model. The primary data source used was all Islamic Education subject matters contained on the Islamic Education textbook at the Middle School level published by the Ministry of Education and Culture. The data collection technique used is the documentation technique with an in-depth reading mechanism. The findings reveal that there are four gender constructs contained in the Islamic History content, namely: (1) applying the patriarchal culture, (2) placing men as the main character, (3) prioritizing men existence and his roles, and (4) marginalizing the existence and role of women.